Correcting the light extinction effect of fly ash particles on the measurement of NO by TDLAS - Guo, Songjie; Yang, Yan; Shao, Guodong; Li, Zhenghui; Ren, Wei; Mo, Juehui; Lu, Zhimin; Yao, Shunchun (Frontiers in Physics, 2022)
The measurement of nitric oxide (NO) concentration in power plant flue gas by tunable diode laser absorption spectroscopy (TDLAS) is susceptible to fly ash particles. The presence of fly ash particles causes laser intensity fluctuations and leads to the second harmonic (2f) signal amplitude changes. In this manuscript, we analyzed the influence of particles on the 2f signal and corrected the measurement error of NO concentration by the wavelength modulation-second harmonic (WMS-2f) technique. Specifically, the 2f signal error caused by quartz sand and fly ash particles were measured, and the exponential function representing the peak-to-peak error of the 2f signal was obtained by fitting. Finally, the peak-to-peak value of the 2f signal and the NO concentration were corrected according to the exponential function. After correction, the NO concentration error under the fly ash influence (the particle size in the range of 10-200 μm and the mass concentration is less than 18.26 g/m3) was no more than 2%. This correction method effectively improves the measurement accuracy of NO concentration by the WMS-2f technique in the fly ash environment.